2021
DOI: 10.1091/mbc.e21-04-0174
|View full text |Cite
|
Sign up to set email alerts
|

Survey of cancer cell anatomy in nonadhesive confinement reveals a role for filamin-A and fascin-1 in leader bleb–based migration

Abstract: Cancer cells migrating in confined microenvironments exhibit plasticity of migration modes. Confinement of contractile cells in a non-adhesive environment drives ‘leader bleb-based migration’ (LBBM), morphologically characterized by a long bleb that points in the direction of movement separated from a cell body by a contractile neck. Although cells undergoing LBBM have been visualized within tumors, the organization of organelles and actin regulatory proteins mediating LBBM is unknown. We analyzed the localiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…In summary, our data suggests a mechanism of amoeboid motility for immune cells that is alternative, yet complementary to the previously described mechanism of amoeboid motility in non-immune melanoma cells (Adams et al, 2021; Logue et al, 2015). Briefly, the basis of amoeboid cell motility in melanoma cells is a cortex treadmilling within the lasting leader bleb that powers friction-based cell sliding within an ideal “sandwich”-like microenvironment, i.e.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…In summary, our data suggests a mechanism of amoeboid motility for immune cells that is alternative, yet complementary to the previously described mechanism of amoeboid motility in non-immune melanoma cells (Adams et al, 2021; Logue et al, 2015). Briefly, the basis of amoeboid cell motility in melanoma cells is a cortex treadmilling within the lasting leader bleb that powers friction-based cell sliding within an ideal “sandwich”-like microenvironment, i.e.…”
Section: Resultssupporting
confidence: 84%
“…This conjecture is based on the observation of amoeboid sliding motility in non-immune melanoma cells, where an excessive cross-linking of contractile cortical F-actin ( e.g. by filamin-A and/or fascin), combined with the cells sterical confinement, results with cortex reorganization into a continuous system of coaxial circumferential fibers, forming an elongated cylindrical cortex of a leading bleb (Adams et al, 2021). We suggest that the reported filamin-A and/or fascin-rich circumferential cortical structures in melanoma cells and the observed discrete septin-positive cortical rings in human T cells are both analogous to the linear stress-fibers from the perspective of the actomyosin organization and condensation dynamics, yet in a circular form, locking onto themselves within the cortex, rather than onto the adhesive focal adhesions (Adams et al, 2018; Liu et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition Fascin overexpression upregulates expression and recruitment of MMPs, supporting a role for Fascin in ECM remodeling what also facilitate mesenchymal motility of cells ( Al-Alwan et al, 2011 ). It was recently shown that in special condition (under conditions of confinement and low substrate adhesion) the increase of Fascin expression promotes the transition of melanoma and osteosarcoma cells to amoeboid migration ( Clancy et al, 2019 ; Adams et al, 2021 ).…”
Section: The Selection Of Individual Cytoskeleton Proteins As Drug Ta...mentioning
confidence: 99%
“…This seeming contradiction could be explained by the fact that disruption of focal adhesions prevents cell migration by a mesenchymal mechanism, but can serve as a trigger for the transition to amoeboid movement. It was recently shown that an increase in FLNA expression promotes the transition to amoeboid movement driven by leader bleb (Leader Bleb-Based Migration - LBBM) of melanoma cells under conditions of low adhesion and confinement ( Adams et al, 2021 ). Suppression of FLNA with siRNA significantly reduces the number of cells able to switch to this mode of migration.…”
Section: The Selection Of Individual Cytoskeleton Proteins As Drug Ta...mentioning
confidence: 99%